EEG and MRI findings and their relation with intellectual disability in pervasive developmental disorders - Ünal, Özlem (2009)
BACKGROUND: The diagnostic category pervasive developmental disorders (PDDs) refer to a group of five disorders: autism, Rett syndrome, childhood disintegrative disorder, Asperger syndrome, and pervasive developmental disorder not otherwise specified (PDD-NOS). EEG abnormalities and seizures are considered much frequent in autistic subjects with comorbid intellectual disability (ID). In this study, we aimed to evaluate the EEG and MRI findings and their relation with ID in pervasive developmental disorder. METHODS: A retrospective, cross-sectional and non-experimental study was performed. Subjects included 81 patients diagnosed with autism or PDD-NOS according to the DSM-IV criteria. The age range of the patients was 2–15 years (mean 6.6 years, SD 3.0). Among them, 21 (25.9%) were girls and 60 boys (74.1%). RESULTS: Patients with severe ID had a higher rate of EEG abnormalities (P=0.03) than patients without ID as well as patients with mild or moderate ID. The association remained significant after the structural MRI abnormalities were controlled (P=0.04). The severity of ID was not associated with abnormal MRI. The most frequent EEG and MRI abnormalities were active epileptic anomaly/paroxysmal abnormality and cerebral atrophy/periventricular leukomalacia, respectively. Almost a third of the EEG abnormalities were associated with temporal cortex and adjacent cortical structures. CONCLUSIONS: Consistent with previous studies, almost a fourth of the patients in this relatively large sample of patients with pervasive developmental disorders had EEG and/or MRI abnormalities. EEG results indicate that temporal cortex may play a significant role in pervasive developmental disorders.